2022
DOI: 10.1007/s10633-022-09889-5
|View full text |Cite
|
Sign up to set email alerts
|

Flicker electroretinogram in newborn infants

Abstract: Purpose To develop and validate a flicker electroretinogram (ERG) protocol in term-born neonates as a potential tool for assessing preterm infants at risk of developing retinopathy of prematurity. Methods A custom flicker ERG protocol was developed for use with the hand-held RETeval® electrophysiology device. Feasibility of measuring flicker ERG through closed eyelids and without mydriasis was established in a pilot study enabling optimisation of the test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…From previous recordings in term-born infants, we knew that movements of infants during recording led to noisier and less reproducible ERG waveforms. (29) With this in mind, we tried to test the infants in optimal conditions. We recorded ERGs while infants were sleeping, after feeding when possible, and ensured that they were in a comfortable position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Flicker electroretinogram in preterm infants

Gerth-Kahlert,
Taner,
Hanson
et al. 2023
Preprint
Self Cite
“…From previous recordings in term-born infants, we knew that movements of infants during recording led to noisier and less reproducible ERG waveforms. (29) With this in mind, we tried to test the infants in optimal conditions. We recorded ERGs while infants were sleeping, after feeding when possible, and ensured that they were in a comfortable position.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of testing, Myo-Trace® electrodes were the only electrodes commercially available that were physically small enough to be used in extremely preterm infants. To compare data obtained in prematurely born infants with those previously obtained in term-born babies using different electrodes (29), we carried out an electrode comparison in a new infant cohort. Our icker ERG protocol was used to test both eyes of 10 term-born infants, using Myo-Trace® electrodes in the rst eye followed by RETeval Sensorstrip® (LKC Technologies Inc.) electrodes in the fellow eye.…”
Section: Flicker Erg Recordingmentioning
confidence: 99%

Flicker electroretinogram in preterm infants

Gerth-Kahlert,
Taner,
Hanson
et al. 2023
Preprint
Self Cite
“…Interestingly, ERG parameters associated with the development of mild ROP symptoms were comparable to those of healthy subjects later in life, while the two infants who progressed to severe ROP in the study exhibited reduced light-adapted b-wave sensitivity and saturated amplitudes prior to treatment 42 . More recently, a study reported measurable RETeval ERG recordings performed with the skin sensor strip electrodes and closed eyelids 43 , strengthening the value of the portable device as a gentle procedure in a more vulnerable patient population.…”
Section: Introductionmentioning
confidence: 93%
“…Figure 2 illustrates the device and example waveforms. Many publications have emerged reporting its use in diverse conditions including diabetic retinopathy, a range of inherited retinal diseases, birdshot chorioretinopathy, glaucoma, idiopathic intracranial hypertension, and others [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Advances In Devicesmentioning
confidence: 99%
“…These are summarised in Table 3. Some have been incorporated in portable devices, with findings reported in several studies [3,31,33,35,36,39]. An ISCEV guide has been published reviewing the range of standard and extended protocols [53].…”
Section: Advances In Devicesmentioning
confidence: 99%